2020
DOI: 10.1177/0268355519896729
|View full text |Cite
|
Sign up to set email alerts
|

The risk of lower-limb superficial vein thrombosis relative to lower-limb venous thrombotic events is not increased in winter months

Abstract: Objectives Ambient temperature (that impacts differently venous flow in superficial and deep veins) could have a different effect on the risk of superficial and deep venous thrombosis. We searched for a trimestral variation of the risk of superficial venous thrombosis among all lower-limb thrombotic events (lower-limb thrombotic events = superficial venous thrombosis + deep venous thrombosis). Methods We retrospectively analyzed the results of venous ultrasound investigations performed among 11,739 patients (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A small retrospective study showed an increase in the summer months; a possible explanation could be the poor compliance of patients to pharmacologic therapy and elastic stockings [15]. Other reports [16,17] did not confirm such an observation, although a small increase was observed in summer [17].…”
Section: Epidemiologymentioning
confidence: 91%
“…A small retrospective study showed an increase in the summer months; a possible explanation could be the poor compliance of patients to pharmacologic therapy and elastic stockings [15]. Other reports [16,17] did not confirm such an observation, although a small increase was observed in summer [17].…”
Section: Epidemiologymentioning
confidence: 91%